Tafsir Isyari atas Konsep al-Khalq, al-Insāniyyah, dan al-Nubuwwah dalam Kitab al-Wāridāt al-Ilāhiyyah - Djuned, Muslim; Harizi, Hasvi; Misnawati, Misnawati; Khairizzaman, Khairizzaman (Institut Agama Islam Negeri Kediri, 2025)
The book al-Wāridāt al-Ilāhiyyah fī al-Tafsīr ‘alā Ṭarīqati al-Ṣūfiyyah bi al-Isyārah wa Ṣarīḥ al-‘Ibārah by Muhammad al-Bayṭār is a Sufi interpretation of the Qur’an that has received limited attention in academic studies, especially concerning the meanings of creation (al-khalq), humanity (al-insāniyyah), and prophethood (al-nubuwwah). This study aims to explore how these three concepts are interpreted within a Sufi framework. The method used was a qualitative literature-based study with an ishārī interpretation approach and thematic analysis. The primary source is the 2005 printed edition by Dār al-Kitāb al-‘Arabī, focusing on selected sections (wāridāt) that convey spiritual symbolism. The findings show that creation in this tafsir is viewed as a process of tajallī (divine manifestation), positioning humans as mirrors of the cosmos. Humanity is portrayed as a spiritual journey toward the knowledge of God (ma‘rifah), while prophethood represents the highest form of human perfection (insān kāmil), particularly as embodied in the figures of Prophet Adam and Prophet Muhammad. This tafsir is structured thematically and blends philosophical Sufism with Qur’anic symbolism.The study concludes that the book al-Wāridāt al-Ilāhiyyah deserves recognition as an important reference in Sufi exegesis. It contributes to enriching alternative approaches to understanding the Qur’an and encourages further philological and comparative studies of the work within the context of contemporary Qur’anic scholarship.